On the definition and measurement of chronic poverty - Rolf Aaberge; Magne Mogstad (Institute for the Study of Labor (IZA), 2007)
As an alternative to the conventional methods for measuring chronic poverty, this paper proposes an interpersonal comparable measure of permanent income as a basis for defining and measuring chronic poverty. This approach accounts for the fact that individuals regularly undertake inter-period income transfers. Moreover, the approach allows for individual-specific interest rates on borrowing and saving as well as for the presence of liquidity constraints. Due to the general nature the proposed method proves useful for evaluating the theoretical basis of the standard methods for measuring chronic poverty.
urn:nbn:de:101:1-20080415162
Keywords: 330; Armut; Einkommen; Intertemporale Allokation; Lebenszyklus; Messung; Theorie